Comparison AHP-MABAC And Waspas Methods For Supplier Recommendations - Wina Yusnaeni; Marlina Marlina; Ratih Yulia Hayuningtyas; Retno Sari (Universitas Bina Sarana Informatika, 2021)
The procurement of the goods or services of a company is determined by qualied suppliers. Therefore, it is necessary for a company to choose and evaluate the suppliers that have cooperated based on the required criteria. The purpose is that all of the suppliers can compete in improving the quality and their consistency as a supplier to the company. The process to decide the appropriate supplier in this study is multicriteria support decision methods that can help in the consistency's criteria and the accuracy of the decision. Here we perform the calculation criteria for consistency with the AHP method that will further calculate the weight of criteria and alternatives against the criteria using the method of MABAC and WASPAS. The results of the data comparison using the method of MABAC have actual results with the suppliers recommended and not recommended compared to the method of WASPAS.